AB0346 Safety and efficacy of rheumatoid arthritis treatment with modified-release prednisone (mr-pdn), experience in "real life". (23rd January 2014) - Sola, D.; Nerviani, A.; Molinari, R.; Rossi, L.; Cerutti, C.; Bellan, M.; Menegatti, M.; Pirisi, M.; Sainaghi, P. P.
Abstract : Background: Glucocorticoids (GC) are commonly used for rheumatoid arthritis (RA) treatment with concerns about their side effects. A modified-release formulation of prednisone (MR-PDN) allows the release of the drug during the night when plasma concentrations of pro-inflammatory cytokines are highest. In RCT, this formulation had greater effectiveness than traditional one at equal dosage on both morning stiffness and disease activity reduction. However, these results need to be confirmed in "real life" clinical practice. Objectives: To assess in "real life" adherence to treatment and efficacy (morning stiffness, DAS28 score and steroid dose reduction) in RA patients who initiated treatment with MR-PDN, Methods: We performed a retrospective evaluation of clinical records of RA patients followed at tertiary level immuno-rheumatology unit affiliated to a medical school from January 2011 till December 2012. We included any RA patient who started RM-PDN and completed at least 12 W follow up. Side effects, compliance to treatment, treatment discontinuation, DAS28 score, morning stiffness duration, steroid dose, were obtained from clinical records. Variables were assessed with parametric analysis or X 2 when appropriate. Results: 64 RA patients who initiated RM-PDN completed a 12 weeks (W) follow-up, 49 completed 24 W and 33 48W. In 19 patients this was the first steroid treatment, 45 received MR-PDN after a switch from one other steroid (in this case 1 month bridging with traditional steroid was performed). At 12 W 55/64 patients remained on treatment (86%), at 24 W 38/49 (78%), at 48 W 21/33 (64%). Causes for discontinuation were: gastric intolerance 3/12 (25%), rebound of joint symptoms 3/12 (25%), malaise / fatigue 6/12 (50%). The efficacy analysis was limited only to patients with DMARDs or biological therapies stable for the whole period of observation. Of these, 41 have completed a 12 W follow-up, 29 a 24 W follow up and 19 a 48 W observation. The mean DAS28 at baseline was 3.6 ± 0.6 with reduction to 3.0 ± 0.8 at 12W, 2.9 ± 0.9 at 24W and 2.8 ± 0.9 at 48W (p <0.002 vs baseline for any observation time, t-test for paired samples). At baseline, 24% had a DAS28 <3.2 while this proportion rose to 64% at 12W, 66% at 24W and 71% at 48W (p <0.001 vs baseline for each follow-up, χ2 test). Similarly, while at baseline 57% of patients had a morning stiffness lasting ≥ 45′ this proportion reduced to 10% at 12W, 9% to 24% and 5% at 48W (P <0.0001 vs. baseline each follow-up, X2 test). Finally, the mean dose of steroid used (in PDN equivalent) reduced from 4.9 ± 0.5 mg to 4.7 ± 0.9 at 12W, 4.2 ± 1.9 at 24W and 3.6 ± 1, 6 at 48W (p <0.03 vs. baseline, t-test for paired samples for 24 and 48W). Conclusions: In RA patients in "real life" the use of MR-PDN showed good safety profile and adherence to treatment also after switch from prolonged traditional steroid treatment. We observed a reduction in morning stiffness and disease activity similarly to that described in clinical trial. The greatest improvement occurs within the first 12 weeks confirmed by further modest improvement up to 48 weeks. Finally the use of the MR-PDN permitted a lower consumption of steroid in these patients with obvious long term benefits. Disclosure of Interest: None Declared